Co‐existence of psoriasis and melanoma in a large urban academic centre population: a cross‐sectional retrospective study. (27th January 2015) - Bhattacharya, T.; Nardone, B.; Rademaker, A.; Martini, M.; Amin, A.; Al‐Mudaimeagh, H.M.; Kiguradze, T.; Schneider, D.; West, D.P.
Abstract: Background: Psoriasis has been linked to increased malignancy risk, particularly lympho‐haematopoietic and non‐melanoma skin cancers; however, its association with cutaneous melanoma remains unclear. Objective: The aim of this study was to determine if there is an association between melanoma and psoriasis in a large, urban academic population through an electronic medical record database. Methods: We searched our institution's electronic medical record database (EDW‐Electronic Data Warehouse) from 1/2001 to 11/2013. Subjects were identified by ICD‐9 codes. Melanoma diagnosis was included only if documented at least 1 month after the psoriasis diagnosis was documented. Odds ratio (OR) was obtained for association between cutaneous melanoma and psoriasis. The OR was then adjusted for phototherapy and age. To minimize detection bias, we also obtained the OR for association between cutaneous melanoma and atopic dermatitis. Results: We identified 10 947 patients with psoriasis, 64 of whom had a subsequent diagnosis of cutaneous melanoma. We detected a significant association between melanoma and psoriasis (OR = 1.77; 95%CI 1.38–2.26; P  < 0.0001; total n  = 1 525 252). After adjusting for phototherapy and age, a statistically significant association between melanoma and psoriasis remained detectable (OR = 1.9; 95%CI 1.55–2.55; P  < 0.0001 and OR = 1.64; 95%CI 1.17–2.26; P  = 0.003 respectively). The OR for melanoma with atopic dermatitis in the same patient database showed a statistically significant inverse association between the two diseases (OR = 0.35; 95%CI 0.16–0.73; P  = 0.005). Conclusion: Our findings show a statistically significant association between psoriasis and melanoma. After adjusting the OR for phototherapy and age, a statistically significant association remained. Further investigations exploring these associations are warranted in order to establish the relative risk for melanoma in psoriasis patients.